Editorial - Carreño, Omar Asdrubal León (Universidad Santo Tomás, Bogotá, Colombia, 2016)
In this issue, Análisis, Revista Colombiana de Humanidades (Analysis, Colombian Journal of Humanities), wanted to concentrate on education, in a perspective of integrality, that is in line with that which states and faces the University of Santo Tomás of Colombia, institution to which it belongs. The first seven articles focus on this, which account for diverse understandings or converging applications with the concept of integrality.